Integration of fission track thermochronology with other geochronologic methods on single crystals - Danisik, Martin (Springer International Publishing, 2019)
Fission-track (FT) thermochronology can be integrated with the U–Pb and (U–Th)/He dating methods. All three radiometric dating methods can be applied to single crystals (hereafter referred to as “triple-dating”), allowing more complete and more precise thermal histories to be constrained from single grains. Such an approach is useful across a myriad of geological applications. Triple-dating has been successfully applied to zircon and apatite. However, other U-bearing minerals such as titanite and monazite, which are routinely dated by single methods, are also candidates for this approach. Several analytical procedures can be used to generate U–Pb—FT—(U–Th)/He age triples on single grains. The procedure introduced here combines FT dating by LA-ICPMS and in situ (U–Th)/He dating approach, whereby the U–Pb age is obtained as a byproduct of U–Th analysis by LA-ICPMS. In this case, U–Pb, trace element and REE data can be collected simultaneously and used as annealing kinetics parameter or as provenance and petrogenetic indicators. This novel procedure avoids time-consuming irradiation in a nuclear reactor, reduces multiple sample handling steps and allows high sample throughput (predictably on the order of 100 triple-dated crystals in 2 weeks). These attributes and the increasing number of facilities capable of conducting triple-dating indicate that this approach may become more routine in the near future.